Implementasi Model Pembelajaran Inovatif Flipped Classroom Masa Bencana Alam Di SDN Tumbang Rungan - Eshariyani; Akbar, Nadzmi; Rahmi, Agustina (Jurnal Ilmiah Kanderang Tingang, 2024)
The aim of this research is to determine the phenomenon of the innovative flipped classroom learning model during the flood disaster at Public Elementary School Tumbang Rungan, Pahandut District, Palangka Raya City, Central Kalimantan. Using a qualitative approach, data was collected through literature study, observation, interviews, documentation, and analysis of new findings related to the flipped classroom learning model at Tumbang Rungan Elementary School. The findings of the research are as follows: first, elementary school students can learn innovatively from digital teaching materials; second, there is collaboration between teachers and students in facing challenges in the era of digitalization; third, through training and teacher working group activities, school principals and some teachers have prepared themselves to face challenges and find solutions using appropriate learning models to deal with natural disaster problems; fourth, the obstacles faced include: (1) Some of the learning facilities for students have been provided, but the unfavorable natural conditions present a challenge; (2) Some teachers are reluctant to learn due to age factors; (3) Parental support has not been optimal.